Variations in West Nile Virus neuroinvasive infection: A case series of three patients in West Phoenix. (2021) - Mody, Aniket; Singh, Monider; Chhetri, Chandra D.; Castro, Michael; Sanghera, Perminder
Abstract: West Nile Virus (WNV) is the most common mosquito-borne virus in the United States and North America. Although WNV disease occurs on a spectrum ranging from a relatively benign febrile illness to life-threatening neuroinvasive disease, the clinical presentations can vary widely and thus necessitates a high degree of suspicion. Here we describe three such cases where each individual presented with a unique constellation of symptoms that made the diagnosis challenging. It is essential for physicians to be well informed on the differing symptomology so early diagnosis and supportive management can mitigate poor prognosis.